Difusão espacial da COVID-19 em Presidente Prudente e Botucatu - São Paulo - Lima, João Pedro Pereira Caetano de [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The present undergratuade thesis was based on the work developed in the scientific initiation project that aimed to compare the epidemiological situation of COVID-19 in Presidente Prudente and Botucatu, São Paulo, from the application of appropriate technical procedures for the spatial analysis of the occurrence of the disease. Through comparative analyses between the two intermediard cities located in the interior of São Paulo, we sought to analyze and discuss the spatial diffusion and spatial distribution of confirmed cases and deaths by COVID-19, relating them to sociodemographic variables from the 2010 Demographic Census for the studied municipalities. By delving into the intraurban scale, we relied on geospatial techniques and tools to explain and correlate key variables for understanding the spatial patterns of the disease. Among the techniques and tools used, the Kernel estimator, spatial autocorrelation analysis and hot spots analysis stand out. Through the results obtained, it was possible to observe a higher concentration of confirmed cases at the edges of the cities and the concentration of deaths in the central regions. In addition, through an analysis of the epidemiological profile of cases and deaths due to COVID-19, it was possible to observe that the younger, non-white, lower-income population express similar spatial pattern to those observed in COVID-19 and its spatial diffusion in the cities studied. As the results are expressed during the work, it is possible to propose a methodological guide of spatial analysis for COVID-19 in both cities, as well as in other outbreaks of diseases in similar situations, serving as a subsidy for epidemiological surveillance teams.

A presente monografia teve como base o trabalho desenvolvido no projeto de iniciação científica que teve como objetivo comparar a situação epidemiológica da COVID-19 em Presidente e Botucatu, São Paulo, a partir da aplicação de procedimentos técnicos adequados para a análise espacial da ocorrência da doença. Através de análises comparativas entre as duas cidades de porte médio situadas no interior paulista, buscou-se analisar e discutir a difusão espacial e a distribuição espacial dos casos confirmados e óbitos por COVID-19, relacionando-os com variáveis sociodemográficas provenientes do Censo Demográfico de 2010 para os municípios estudados. Ao aprofundar na escala do intraurbano, nos baseamos em técnicas e ferramentas geoespaciais para explicar e correlacionar variáveis chave para a compreensão dos padrões espaciais da doença. Entre as técnicas e ferramentas utilizadas, destaca-se o estimador de Kernel, análises de autocorrelação espacial e análises de pontos quentes. Mediante os resultados obtidos, foi possível observar uma maior concentração de casos confirmados nas bordas das cidades e a concentração de óbitos nas regiões centrais. Além disto, através de uma análise de perfil epidemiológico dos casos e óbitos por COVID-19, foi possível observar que a população mais jovem, não-branca, e de menor renda, expressam um padrão espacial semelhante aos observados da COVID-19 e sua difusão espacial nas cidades estudadas. Na medida que os resultados são expressos durante o trabalho, é possível propor um roteiro metodológico de análise espacial para a COVID-19 nas duas cidades, bem como em outros surtos de doenças em situações semelhantes, servindo de subsídio para as equipes de Vigilância Epidemiológica.
Spatial diffusion of COVID-19 in Presidente Prudente and Botucatu - São Paulo
Keywords: Geography of health; Cartography; Geotechnologies; Spatial analysis; Health surveillance; Geografia da saúde; Cartografia; COVID-19; Geotecnologias; Análise espacial; Vigilância em saúde